Cohort study of the incidence of spontaneous preterm birth and septic abortion referred by pathological examination in Gifu prefecture in Japan. (January 2017) - Takahashi, Yuichiro; Iwagaki, Shigenori; Itoh, Mitsuaki; Nakamura, Hiromi; Kuwabara, Kazuo; Hiraku, Yuka; Hori, Masashi; Misao, Ryo; Furui, Tatsuro; Morishige, Kenichiro
Abstract: Aims: To clarify the incidence of spontaneous preterm birth (PB) and septic abortion (sab) in Gifu prefecture in Japan. Study design: This prospective, population-based cohort study was approved by our hospital's Institutional Review Board. All 36 hospitals (100%) in Gifu prefecture offering obstetrical services participated in the study. Patient enrollment criteria were: sab and PB from 22 to < 37 weeks gestation (WG), excluding for maternal and fetal indications. Pathological examinations before 36 WG and associated factors for both PB and chorioamnionitis (CAM) stage 3 were analyzed by multiple logistic regression analysis judging from minimum daily clinical information in Gifu prefecture. Results: The sab rate per all deliveries was 29/16871 (0.17%) at 16.9 ± 2.9 WG. The total spontaneous PB rate was 615/16871 (3.65%) at 34.5 ± 2.7 WG, with birth weight (BW) 2267 ± 557 g. There were 26 (0.15%) PBs from 22 + 0 to 27 + 6 WG (weeks + days) at 25.2 ± 1.5 WG, with BW 745 ± 199 g. Among 214 pathological examinations, CAM was detected in 80% (sab) and 63% (PB < 36 WG), respectively. Funisitis were 14% and 17% respectively. Episodes of serial genital bleeding and/or hematoma at < 12 WG were more frequent in sab and earlier PB (< 28 WG) associated with CAM stage 3 (odds 1.9, P < 0.0001). Combined factors such as bleeding and past history of CAM correlated with earlier delivery at 23.4 ± 5.9 WG (P = 0.0032). Conclusion: In Gifu prefecture, the incidence of sab was 0.17% (per all deliveries) and 3.65% of spontaneous PB. The combined risk of past CAM history and bleeding was associated with earlier delivery among total preterm birth.